Controlled interkingdom cell-cell communication between Saccharomyces cerevisiae and Bacillus subtilis using quorum-sensing peptides - Vološen, Tomislav; Gutbier, Uta; Korn, Ramón; Korp, Juliane; Göttsche, Tobias; Schuster, Linda; Pohl, Carolin; Rau, Cindy; Wolf, Diana; Ostermann, Kai (Frontiers in Microbiology, 2024)
Understanding communication among microorganisms through the array of signal molecules and establishing controlled signal transfer between different species is a major goal of the future of biotechnology, and controlled multispecies bioreactor cultivations will open a wide range of applications. In this study, we used two quorum-sensing peptides from Bacillus subtilis – namely, the competence and sporulation factor (CSF) and regulator of the activity of phosphatase RapF (PhrF)—to establish a controlled interkingdom communication system between prokaryotes and eukaryotes. For this purpose, we engineered B. subtilis as a reporter capable of detecting the CSF and PhrF peptides heterologously produced by the yeast Saccharomyces cerevisiae. The reporter strain included the ComA-dependent srfAA promoter fused to the bioluminescence or fluorescence reporter gene(s) to monitor promoter activity measured in a multimode microplate reader. The first measurements of srfAA promoter activity showed a specific response of the reporter strain to the peptides CSF and PhrF. Based on this, systematic mutagenesis of genes that modulate the activity of ComA in the reporter strain resulted in increased activity of the promoter and, thereby, higher sensitivity to the heterologously produced CSF/PhrF. The robustness of the signal transfer was further confirmed in co-cultivation studies in both liquid and solid media. The reporter strain exhibited an up to 5-fold increase in promoter activity in the presence of quorum-sensing peptides-producing cells of S. cerevisiae. In summary, a quorum sensing peptide-driven interkingdom crosstalk between yeast and bacteria was successfully established, which might serve as a basis for controlled protein expression in co-cultivations, establishing biological sensor–actuator systems or study cell-cell interaction and metabolite exchange in bioreactors cultivations.